Oxidative stress-induced textural and biochemical changes of scallop Patinopecten yessoensis adductor muscle under heat treatment. Issue 1 (1st January 2018) - Dong, Xiufang; Fu, Hui; Feng, Dingding; He, Baoyu; Jiang, Di; Qin, Lei; Qi, Hang
ABSTRACT: In this study, the effects of heat treatment (45°C and 65°C, respectively) on the quality of Patinopecten yessoensis adductor muscle (PYAM) were investigated. Water mobility in PYAM samples was analyzed using low-field nuclear magnetic resonance. The texture of treated PYAM was analyzed using texture profile analysis. Protein degradation was characterized using SDS-PAGE. Activities of cathepsin L (CL), superoxide dismutase (T-SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) were determined using chemical analysis methods. The production of free radicals was measured using electron spin resonance. It was revealed that water mobility in PYAM samples increased with the extension of heated time. Cohesiveness of PYAM was higher in samples heated at 65°C than at 45°C, while hardness showed an opposite trend, higher in the samples heated at 45°C than at 65°C. The degradation of structural proteins was more severe in the samples heated at 65°C than at 45°C, with the greater CL activity being observed. It was also found that heating caused elevation in T-SOD, GSH-Px, and CAT enzyme activities. Considering the chemical changes in the PYAM samples, contents of carbonyl and malonaldehyde increased, but sulfhydryl content decreased with heating. Level of free radicals increased significantly from 6 h on after heat treatment, with higher level at 65°C than at 45°C. These results suggested that oxidative stress is directly involved in quality changes during heat treatment of PYAM.